Propaganda i rzeczywistość nazistowska widziana oczami dziecka w powieści Johna Boyne’a Chłopiec w pasiastej piżamie - Moskała, Paweł (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The aim of the article is to present the Nazi reality and its propaganda as seen through the eyes of Bruno – the hero of the novel John Boyne’s The Boy in the Striped Pyjamas. The narrative shown from the perspective of a child reveals, in a unique way, the mechanics of demagogy and manipulation used by the Nazi propaganda. The symbolic fence between Bruno, the son of the concentration camp commandant, and a Jewish boy of the same age named Schmul, becomes the main theme of the novel. The story of the novel reveals the entanglement of the children in the workings of the history. Such a story construction is a starting point for the author of the article for the analysis of the complexity of propaganda measures and their influence on a young person, mainly in the affective, intellectual and social dimensions. The analysis involves not only the linguistic layer of the novel, but also the topography of the place and the characteristic use of Nazi symbols.